Restoration of the structure and soil protection role of no-till in chernozems and chestnuts soils of the Stavropol Territory - S. A. Yudin; N. R. Ermolaev; V. P. Belobrov; V. K. Dridiger; R. G. Gadzhiumarov; N. V. Yaroslavtseva; I. A. Nadutkin (Бюллетень Почвенного института им. В.В. Докучаева, 2024)
The results of research on the example of southern chernozem and chestnut soil are presented. Long-term use of plowing with rotation of the soil layer and the use of fallows leads to a critical state of the soil in terms of the content of aggregates measuring >10 mm and >1 mm. The introduction of notill on old arable soils leads to a general increase in the mean weighted diameter of aggregates (MWD). The intensity of restoration of the structural state of the soil during no-till in southern chernozem occurs more intensively than in chestnut soil, and the main changes are recorded in the fractions of agronomically valuable aggregates. In southern chernozem there is an increase in diameter from 6.0 mm to 9.5 mm, while in chestnut soil the MWD increases only to 7 mm. The content of erosion-susceptible aggregates <1 mm and their change depending on the intensity of agricultural cultivation in southern chernozem and chestnut soil indicates a tendency to restore the structure in the no-till variant. In southern chernozem, the content of particles of 1–0.5 mm size decreased by 1.2%, and in chestnut soil – by 6.2%. Refusal of mechanical tillage showed that, in contrast to dry aggregates, the influence of no-till on the water stability of the structure of the arable horizon is more significant and is presented in the form of fractions rearrangement. The use of no-till technology results in a reduction in the content of erosion-susceptible aggregates and increases the water stability of the structure of the arable horizon, which, together with the influence of crop residues on the soil surface, provides an anti-erosion effect. The restoration of the structural state of the soil during notill in southern chernozem proceeds more intensively than in chestnut soil. The main changes in the form of rearrangement occur in fractions of agronomically valuable aggregates.